2016
DOI: 10.1103/physrevb.94.035101
|View full text |Cite
|
Sign up to set email alerts
|

Spin susceptibility and electron-phonon coupling of two-dimensional materials by range-separated hybrid density functionals: Case study ofLixZrNCl

Abstract: We investigate the capability of density functional theory (DFT) to appropriately describe the spin susceptibility, χs, and the intervalley electron-phonon coupling in LixZrNCl. At low doping, LixZrNCl behaves as a two-dimensional two-valley electron gas, with parabolic bands. In such a system, χs increases with decreasing doping because of the electron-electron interaction. We show that DFT with local functionals (LDA/GGA) is not capable of reproducing this behavior. The use of exact exchange in Hartree-Fock … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…However, in general, the effective mass of HfNCl is slightly larger than that of ZrNCl. Similarly, N (0) is larger in HfNCl than ZrNCl for all doping 26 .…”
Section: A Electronic Structurementioning
confidence: 88%
See 3 more Smart Citations
“…However, in general, the effective mass of HfNCl is slightly larger than that of ZrNCl. Similarly, N (0) is larger in HfNCl than ZrNCl for all doping 26 .…”
Section: A Electronic Structurementioning
confidence: 88%
“…In previous work, it has been shown that in 2D mul-tivalley semiconductors, at low doping, the electronelectron interaction enhances intervalley electron-phonon coupling, explaining the behavior of T c 25,26 . The enhancement of T c is linked to the enhancement of the spin susceptibility χ s .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, it is now possible to force the total spin to assume noninteger values, which often happens to be the case for the ground state in magnetic metals. This also allows to compute the static spin susceptibility χ s = ∂M s / ∂B , where M s is the spin magnetization and B the magnetic field, by finite differences using the formula χ s = ( ∂ 2 E tot / ∂M s 2 ) −1 (Pamuk, Baima, Dovesi, Calandra, & Mauri, ).…”
Section: New Featuresmentioning
confidence: 99%